Adiagnostic Study of the Giardia Lamblia Parasite Genotypes, Which Causes Diarrhea among the Patients in Najaf, Province, by Using the PCR Technique - Jameel Jerri Yousif; Widad Hashim Yahya (Kufa Journal for Nursing Sciences)
Objective: It aims to study the prevalence of the Giardia lamblia parasite and identify genotypes of the parasite in patients with diarrhea in the province of Najaf by using the microscopic examination and the polymerase chain reaction (PCR).